A comparative analysis of crisis communication strategies: handling faculty academic misconduct and sexual misconduct in Chinese higher education institutions - Jiang, Xiaoyu; Kamarudin, Syafila; Mahamed, Mastura; Guo, Jingjing; Wu, Xuanyi (SAGE Publications, 2025)
Chinese higher education institutions are facing an increasing threat of campus crises, especially the academic and sexual misconduct of faculty members, which have caused severe impacts on the reputation and development of universities and colleges. Crisis communication strategies are one of the critical measures for universities and colleges to eliminate or mitigate crises and maintain their reputation and growth. However, few studies are exploring the crisis communication strategies employed by Chinese universities and colleges in response to crises. This study employs quantitative content analysis to examine the crisis communication strategies utilized by Chinese higher education institutions in response to faculty academic misconduct and sexual misconduct crises. The study specifically focuses on the institutions’ responses on official platforms. Applying the Situational Crisis Communication Theory (SCCT) and Image Repair Theory (IRT) frameworks, this study examines the official statements released by Chinese colleges and universities in response to allegations made on official platforms such as Sina Weibo, WeChat, and official websites. Crises investigated belong to the preventable crisis type, which is defined by instances of organizational wrongdoing and concerns caused by human actions. The results reveal five commonly employed crisis communication strategies: corrective action, adjusting information, reminder, bolstering, and victimage, with a notable emphasis on adjusting information and corrective action being the most frequently utilized approach for academic and sexual misconduct crises. There are correlations between the type of crisis (academic and sexual misconduct events) and the application of specific crisis communication strategies (denial and excuse). One significant finding is the limited differentiation observed between crisis response strategies for academic and sexual misconduct crises within the Chinese context. IRT and SCCT have partial adaptability in the non-profit field of China’s higher education, among which IRT exhibits wider applicability than SSCT. This study contributes to crisis management teams and policymakers recognizing and adapting strategies based on academic and sexual misconduct events, promoting more effective crisis management and prevention measures.